Roads and Controversies: MERCOSUR Ten Years afterthe Entry Into Force of the Olivos Protocol - Bas Vilizzio, Magdalena (2014)
The ten years since the Olivos Protocol entered into force represent a mile-stone in Mercosur’s dispute-resolution system. In this sense, this paper aims to analyze the antecedents of the present system (Annex III of Asuncion Treaty and Brasilia Protocol), and evaluate the present conflict-resolution mechanisms, with special reference to the innovations introduced in this respect and disputes resolved under the Olivos Protocol. Finally, the article analyzes some of the possible paths that the dispute-resolution system might take in the future.